Amplicon-Based NGS Panels for Actionable Cancer Target Identification in Follicular Cell-Derived Thyroid Neoplasia - Madsen, Majbritt Busk; Kiss, Katalin; Cilius Nielsen, Finn; Bennedbæk, Finn Noe; Rossing, Maria (Frontiers in Endocrinology, 2020)
Follicular cell-derived thyroid cancers are heterogenous and morphological classification is a complex and highly specialized task. Hence, identification of somatic alterations could provide insights to tumor biology and serve as an add-on diagnostic tool. Also, results from these add-on tools could point in the direction of a more personalized treatment strategy. In the present study we set out to identify and validate the somatic mutation profile in a sample-set of follicular cell-derived thyroid neoplasia. One-hundred-and-one archived formalin fixed paraffin embedded (FFPE) tissue samples from patients diagnosed with follicular cell-derived thyroid neoplasia were included, and upon DNA-extraction and qualitative measurements 99 samples were eligible for amplicon-based next-generation-sequencing. Libraries were generated using the TruSeq Amplicon Cancer Panel, followed by sequencing using a MiSeq. Upon data processing and variant filtering all variants were manually assessed to exclude false positive mutations in the final curated list. Moreover, hot-spot mutations were validated using an independent platform from Agilent. Each diagnostic group were correlated to mutation burden and individual mutations were classified according to recent guidelines for somatic mutation classification. Close to 100% of the archived FFPE samples, were eligible for DNA-library preparation and amplicon sequencing based on DNA quality criterion. The distribution of mutations in the specific diagnostic groups resulted in a higher mutation frequency among the most dedifferentiated than in the groups with a more differentiated cell profile. Based on the distribution mutations across the samples and using hierarchical clustering, we generated four tentative mutational signatures; highly mutated tumors; tumors with mainly NRAS and TP53 mutations; BRAF mutated tumors and tumors with none or single sporadic mutations. Future studies including more samples and follow-up data may amend these signatures, however our results imply that morphological classification of follicular cell derived thyroid neoplasia could be supplemented with a somatic mutational signature. Taken together, broad screening of the somatic alterations in FFPE tissue of thyroid neoplasia is comprehensible and essential for future identification of possible treatment targets and personalized medicine.